Transplant outcomes of 100 cases of living-donor ABO-incompatible kidney transplantation - Saifu Yin; Qiling Tan; Youmin Yang; Fan Zhang; Turun Song; Yu Fan; Zhongli Huang; Tao Lin; Xianding Wang; Yuanyuan Ji (Chinese Medical Journal, 2022)
Abstract. Background:. Although ABO-incompatible (ABOi) kidney transplantation (KT) has been performed successfully, a standard preconditioning regimen has not been established. Based on the initial antidonor ABO antibody titers, an individualized preconditioning regimen is developed, and this study explored the efficacy and safety of the regimen. Methods:. From September 1, 2014, to September 1, 2020, we performed 1668 consecutive living-donor KTs, including 100 ABOi and 1568 ABO-compatible (ABOc) KTs. ABOi KT recipients (KTRs) with a lower antibody titer (≤1:8) were administered oral immunosuppressive drugs (OIs) before KT, while patients with a medium titer (1:16) received OIs plus antibody-removal therapy (plasma exchange/double-filtration plasmapheresis), patients with a higher titer (≥1:32) were in addition received rituximab (Rit). Competing risk analyses were conducted to estimate the cumulative incidence of infection, acute rejection (AR), graft loss, and patient death. Results:. After propensity score analyses, 100 ABOi KTRs and 200 matched ABOc KTRs were selected. There were no significant differences in graft and patient survival between the ABOi and ABOc groups (P = 0.787, P = 0.386, respectively). After using the individualized preconditioning regimen, ABOi KTRs showed a similar cumulative incidence of AR (10.0% υs. 10.5%, P = 0.346). Among the ABOi KTRs, the Rit-free group had a similar cumulative incidence of AR (P = 0.714) compared to that of the Rit-treated group. Multivariate competing risk analyses revealed that a Rit-free regimen reduced the risk of infection (HR: 0.31; 95% CI: 0.12–0.78, P = 0.013). Notably, antibody titer rebound was more common in ABOi KTRs receiving a Rit-free preconditioning regimen (P = 0.013) than those receiving Rit. ABOi KTRs with antibody titer rebound had a 2.72-fold risk of AR (HR: 2.72, 95% CI: 1.01–7.31, P = 0.048). ABOi KTRs had similar serum creatinine and estimated glomerular filtration rate compared to those of ABOc KTRs after the first year. Conclusions:. An individualized preconditioning regimen can achieve comparable graft and patient survival rates in ABOi KT with ABOc KT. Rit-free preconditioning effectively prevented AR without increasing the risk of infectious events in those with lower initial titers; however, antibody titer rebound should be monitored.